Realising the food security benefits of canned fish for Pacific Island countries. (February 2019) - Bell, Johann D.; Sharp, Michael K.; Havice, Elizabeth; Batty, Michael; Charlton, Karen E.; Russell, Joanna; Adams, Wayne; Azmi, Kamal; Romeo, Alessandro; Wabnitz, Colette C.C.; Andrew, Neil L.; Rodwell, Leonard; et al.
Abstract: Canned fish is a healthy alternative to the poor-quality, imported, processed foods implicated in the rise of non-communicable diseases in Pacific Island countries. Increased availability and consumption of canned fish also promises to help fill the gap between sustainable coastal fish production and recommended intake of fish for good nutrition. This study estimates the recent contribution of canned products to fish supply in Fiji, Papua New Guinea (PNG) and Solomon Islands, based on the quantities of imported and locally-produced canned fish sold on domestic markets. The greatest quantities of canned fish were sold in PNG, however, average annual consumption of canned fish per capita was highest in Fiji (8.8 ± 1.3 kg) and Solomon Islands (5.9 ± 0.6 kg), where it supplied an average of 25 ± 4% and 17 ± 2% of recommended dietary fish intake, respectively. Canned tuna comprised an average of 53 ± 2% of the canned fish consumption in Fiji and 92 ± 1% in Solomon Islands. Key actions needed to maintain/increase per capita consumption of canned fish in Pacific Island countries include promoting the health benefits of canned tuna to help combat non-communicable diseases, and facilitating distribution of locally-canned products, especially to the inland population of PNG. Increasing the market share of locally-canned tuna by assisting national canneries to obtain sufficient supplies of tuna to achieve economies of scale and compete effectively in both domestic and intra-regional canned fish trade, could create more employment and contribute indirectly to local food security. Highlights: Canned fish is a healthy alternative to the poor-quality, imported, processed foods implicated in the rise of non-communicable diseases in Pacific Island countries. Canned fish already supplies 15–25% of recommended fish consumption in some of the larger Pacific Island countries. Increased availability and consumption of canned fish promises to help fill the growing gap between sustainable coastal fish production and recommended intake of fish for good nutrition. Policies are needed to promote the health benefits of canned fish to help combat non-communicable diseases, and to facilitate production and distribution of locally-canned tuna. Increasing the market share of locally-canned tuna could create more employment opportunities and contribute indirectly to local food security.